Product Quality of SMEs Food Production in The Perspective of Islamic Economics - Ilhamudin, Muhamad; Permadi, Lalu Adi (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2024)
This study aims to determine the quality of SMEs product in the food industry which are widely spread in Mataram City. The focus of the research is on tempeh product which are one of the leading products in the city. In addition to analyzing the quality of tempeh products, this study also analyzes aspect of quality of this product from an Islamic economic perspective. In determining respondents as data sources in this study, researchers used purposive sampling techniques. To answer the problem posed, the analysis tool used is the Ideal-Point Model, which is a consumer evaluation of what is perceived with what is desired. This model measures the difference between what is perceived and what consumers want. The result shows that the product quality of SME tempeh is very good. This is indicated by the quality value being at the upper interval class which means that the quality of the tempeh product is in accordance with the wishes of consumers. Based on the Islamic view, respondents have the perception of tempeh products as products with halal ingredients, a good process, and are a valuable offer and useful.